2022
DOI: 10.1177/00420859221086524
|View full text |Cite
|
Sign up to set email alerts
|

Protect Black Women Teachers: Influencing Sustainability Through Mental Health Literacy

Abstract: Critical Black women teachers (BWTs) play a vital role in education. They employ pedagogies that are political in nature and effective in outcome, particularly for Black students in urban schools. However, despite their impact, BWTs leave the profession at rates higher than all other teachers. Therefore, this study engaged sista circle methodology to explore how post-service critical BWTs reflected on their teaching experiences, specifically regarding their mental health and the role it had on their decision t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(201 reference statements)
1
2
0
Order By: Relevance
“…This study thus contributes to psychology literature on gendered racism (e.g., Lewis et al, 2013) to specify Black women's experiences of far-right misogynoir by naming far-right ideologies as manifestations of white and male supremacy, examining far-right misogynoir in Black women's experiences at a predominately white selective liberal arts college, and analyzing how Black women made meaning of far-right misogynoir. Consistent with prior research on Black women's psychological experiences of gendered racism (Spates et al, 2020; Young, 2022) and on the connection between misogynoir and mental health concerns among Black women (Bailey, 2016; Lee & Thomas, 2022), our participants shared that their psychological wellness was at stake due to far-right misogynoir. This finding supports previous research that identified associations between far-right activity and psychological health risks among marginalized students (Albright & Hurd, 2020; Leath et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…This study thus contributes to psychology literature on gendered racism (e.g., Lewis et al, 2013) to specify Black women's experiences of far-right misogynoir by naming far-right ideologies as manifestations of white and male supremacy, examining far-right misogynoir in Black women's experiences at a predominately white selective liberal arts college, and analyzing how Black women made meaning of far-right misogynoir. Consistent with prior research on Black women's psychological experiences of gendered racism (Spates et al, 2020; Young, 2022) and on the connection between misogynoir and mental health concerns among Black women (Bailey, 2016; Lee & Thomas, 2022), our participants shared that their psychological wellness was at stake due to far-right misogynoir. This finding supports previous research that identified associations between far-right activity and psychological health risks among marginalized students (Albright & Hurd, 2020; Leath et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…D. Lee, 1992; Shockley & Cleveland, 2011) support the notion that Black educators who center history and culture of the African diaspora in their teaching are those whose racial identities are rooted in the uniqueness of Black people's lived experiences (i.e., higher nationalist ideology). Similarly, more recent work on Black educators who explicitly seek professional learning and support communities around the broader interests of Black people also suggests that these educators may already arrive ideologically disposed to integrate African American culture in the curriculum (S. J. Lee & Thomas, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, more recent work on Black educators who explicitly seek professional learning and support communities around the broader interests of Black people also suggests that these educators may already arrive ideologically disposed to integrate African American culture in the curriculum (S. J. Lee & Thomas, 2022).…”
Section: Racial Identity Attitudes and Individual Differences Across ...mentioning
confidence: 99%